Prototype of Decision Support System Development in Determining Raskin Recipients Candidate - D. Desriyanti; Didik Riyanto (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Decision-making support systems for beneficiaries deserving of the poor are a decision support system that can be used as a tool for assessing the feasibility of providing assistance. The established system only knows the rankings of the population proposals, the population data that has not been stored in the population database, the population data that has not been integrated with the data category, the criteria data, and value data so it requires the process of data input. In the process of data collection methods used are Interviews, Observation, Documentation, Literature Review while the software development methodology used is Prototype. The process of making software by using Macromedia Dreamweaver, language programming used is PHP, Javascript, HTML, and Cascading Style Sheet (CSS). This research aims 1) Make the development of decision support system in giving assistance for the poor in Cekok Ponorogo. 2) Conduct the mapping for proposed poor family and received assistance in graphic form. The conclusions of the development of decision support systems are; 1) Population data stored in the form of database that facilitate the process of searching data. 2) The Recorded of the proposed data and who received assistance for each hamlet in Kelurahan Cekok Ponorogo in the form of a graph. 3) Reduce errors in the submission the proposed data of potential beneficiaries